1986
DOI: 10.1002/jobm.3620260904
|View full text |Cite
|
Sign up to set email alerts
|

Chemoautotrophic growth of Thiocystis violacea, Chromatium gracile and C. vinosum in the dark at various O2‐concentrations

Abstract: Tlie influence of various 0,-concentrations on chemoautotrophic growth was dcterniincd in thc range from microaerobic t o aerobic conditions. Chromatium vinosurn D, Thiocystis violacea 231 1 and Chromatiurn yracile 25-1 were grown chemoautotropliically using consecutively repeated batch riiltures. Rapid growth of all thrce strains occurred only under microaerobic conditions. Thc fastcst growth (1.c = 0.058) was obtained with Chromatium gracile 25-1 grown in the prcsence of 1 mg 0, . 1 -l. For optimal chemoauto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In darkness M. gracile can grow chemotrophically if oxygen and reduced sulfur compounds are both present (21,22). This explains the accumulation of the bacteria at oxygen levels between 0 and 10 M in the zone where the oxygen and sulfide gradients overlap (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In darkness M. gracile can grow chemotrophically if oxygen and reduced sulfur compounds are both present (21,22). This explains the accumulation of the bacteria at oxygen levels between 0 and 10 M in the zone where the oxygen and sulfide gradients overlap (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…4). Kämpf and Pfennig (22) reported that the best chemotrophic growth conditions for M. gracile were 15 to 30 M O 2 , whereas higher concentrations caused cell lysis. Furthermore, oxygen concentrations of Ͻ10 M still allow bacteriochlorophyll synthesis, which is suppressed at higher concentrations (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that these organisms can oxidize sulphur or sulphide either anaerobically in the light or at the expense of 0 2 in the dark. They can quickly switch their energy metabolism from one mode to the other [53,110]. Purple sulphur bacteria can also grow on H 2 and CO 2 in the light.…”
Section: The [3fe-4s] Clustermentioning
confidence: 99%
“…When copper-catalyzed oxidation of cysteine, GSH, and GASH was measured as described previously (32), the rates were 19, 2.5, and 0.37 M thiol oxidized per min, respectively. Thus, GASH is very resistant to air oxidation, a property which, coupled with the presence of GASSGA reductase activity, may contribute to the ability of some Chromatium species to survive in oxygen (15) and even undergo chemoautotrophic growth on sulfide or thiosulfate under microaerophilic conditions (16,22).…”
mentioning
confidence: 99%